The Brand-Cause Fit in the Advertising Campaign for Sprite’s #YouAreNotAlone - Cachay-Marín, Claudia (2022)
Several authors have determined concepts related to the inclusion of social problems in advertising. One of them is brand-cause fit, which refers to the condition in which a brand and a social problem—with which the target audience feels identified—are conceptually united in a single communication proposal. The purpose of this study was to analyze how university students perceive the brand-cause fit as a communication strategy in Sprite's “You Are Not Alone” campaign. A qualitative methodology was adopted and semi-structured interviews were conducted with 24 university students of which 12 belonged to the LGBT community and 12 were heterosexual. The participants positively perceived the brand-cause fit used as an advertising strategy in Sprite's campaign. Not only do they value the fact that brands include social issues and problems in their communication, but they also claim that it is the brands’ responsibility to do so.